Implementasi Merdeka Belajar Dalam Pembelajaran Pendidikan Agama Islam Pada Pendidikan Menengah - Wahidah, Evita Yuliatul; Gentur, Farham Sumaga Barokah (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Merdeka Belajar is a policy program initiated by the Ministry of Education and Culture of the Republic of Indonesia, aimed at providing flexibility in the administration of learning in schools. Islamic Religious Education (PAI) encompasses a series of lessons delivered both formally in schools and informally or non-formally at home or within the community. This study aims to describe the implementation of Merdeka Belajar in the context of PAI learning at the secondary education level, specifically in the 10th grade at SMK Bhakti Wijaya Kusuma Selaawi Garut. The research utilizes a field-based qualitative approach designed to comprehensively and thoroughly describe, illustrate, and explain the implementation of Merdeka Belajar in PAI learning at SMK Bhakti Wijaya Kusuma. The findings indicate that the application of Merdeka Belajar in PAI education at this school has shown significant improvement. This is evidenced by the fulfillment of several indicators reflecting an increase in students' learning capabilities. Merdeka Belajar also addresses practical issues faced by teachers, such as reducing the burden of their profession through flexible and independent assessment of student learning using various types and forms of evaluation instruments and relieving them from cumbersome administrative tasks. Keywords: Implementation of Merdeka Belajar; PAI Learning; Secondary Education